A multi‐component method to determine pesticides in surface water by liquid‐chromatography tandem quadrupole mass spectrometry - Ramos, Andre; Cosgrove, Stephanie; Villa, Raffaella; Jefferson, Bruce; Campo Moreno, Pablo; Jarvis, Peter; Whelan, Michael J.; Guymer, Ian (Wiley, 2017)
Pesticide pollution of surface water is a major concern in many agricultural catchments The development of rapid and accurate methods for determining pesticide concentrations in water samples is, therefore, important. Here we describe a method for the simultaneous analysis of six pesticides (metaldehyde, quinmerac, carbetamide, metazachlor, propyzamide and pendimethalin) in natural waters by direct aqueous injection with liquid chromatography-tandem mass spectrometry. The method validation showed good linearity from 0.2 to 50.0 µg/L with correlation coefficients between 0.995 and 0.999. Method accuracy ranged from 84 to 100% and precision Relative standard deviation (RSD) from 4 to 15%. The limits of detection for the targeted pesticides ranged from 0.03 to 0.36 µg/L. No significant matrix effects on quantification were observed (t-test). The method was tested on water samples from a small arable catchment in eastern England. Peak concentrations for the determinands ranged from 1 to 10 µg/L.
Keywords: Direct injection; LC-MS/MS; Pesticide pollution; Surface water